(Electro‐)chemical Splitting of Dinitrogen with a Rhenium Pincer Complex. Issue 15 (31st January 2020) - van Alten, Richt S.; Wätjen, Florian; Demeshko, Serhiy; Miller, Alexander J. M.; Würtele, Christian; Siewert, Inke; Schneider, Sven
Abstract : The splitting of N2 into well‐defined terminal nitride complexes is a key reaction for nitrogen fixation at ambient conditions. In continuation of our previous work on rhenium pincer mediated N2 splitting, nitrogen activation and cleavage upon (electro)chemical reduction of [ReCl2 ( L 2)] { L 2 = N(CHCHP t Bu2 )2 – } is reported. The electrochemical characterization of [ReCl2 ( L 2)] and comparison with our previously reported platform [ReCl2 ( L 1)] { L 1 = N(CH2 CH2 P t Bu2 )2 – } provides mechanistic insight to rationalize the dependence of nitride yield on the reductant. Furthermore, the reactivity of N2 derived nitride complex [Re(N)Cl( L 2)] with electrophiles is presented. Abstract : N2 splitting into terminal nitrides by chemical and electrochemical reduction of [ReCl2 {N(CHCHP t Bu2 )2 }] is presented. Comparison of electrochemical data with that of the previously reported, related pincer complex [ReCl2 {N(CH2 CH2 P t Bu2 )2 }] allowed for identifying key parameters that control the efficiency of the reaction sequence, which defines reductive N2 splitting.